2021
DOI: 10.3390/nano12010020
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing MXene Flakes on a Magnetic Fiber Network as a Stretchable, Flexible, Electromagnetic Shielding Fabric

Abstract: A unique self-standing membrane composed of hierarchical thermoplastic polyurethane (TPU)/polyacrylonitrile (PAN) fibers is prepared by the electrospinning technique, followed by a simple dip-coating process. Fe3O4 nanoparticles are uniformly anchored on TPU/PAN fibers during the electrospinning process, enabling the membrane to achieve effective electromagnetic interference shielding (EMI SE) performance. Such a hybrid membrane has a high magnetization of 18.9 emu/g. When MXene (Ti3C2Tx) layers are further lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…Since the PU@GNP exhibits high elasticity, the resistance changes strongly under elongation. , It is suggested that PBE–PU@GNP micro–nanofibrous membranes have excellent electrical performance under a small strain. It was further observed that the resistance slightly increases during the recovery stage, which may be due to the rearrangement of the conducting channels. , …”
Section: Resultsmentioning
confidence: 97%
“…Since the PU@GNP exhibits high elasticity, the resistance changes strongly under elongation. , It is suggested that PBE–PU@GNP micro–nanofibrous membranes have excellent electrical performance under a small strain. It was further observed that the resistance slightly increases during the recovery stage, which may be due to the rearrangement of the conducting channels. , …”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, introduced abundant interfaces between the MS and WPU synergistically contributed to high interfacial polarization of incident EMW. Additionally helpful for the loss of incident EMW was the dipolar polarization produced by localized defects and MS surface terminations (Figure c). The penetrating EMW would also experience multiple reflections derived from the layered structure of MS, extending the propagation paths and increasing the interactions between EMW and MS (Figure b) . Therefore, due to the cooperation of MS and WPU, the composite films demonstrated good EMI shielding performance.…”
Section: Resultsmentioning
confidence: 99%
“…59−61 The penetrating EMW would also experience multiple reflections derived from the layered structure of MS, extending the propagation paths and increasing the interactions between EMW and MS (Figure 4b). 62 Therefore, due to the cooperation of MS and WPU, the composite films demonstrated good EMI shielding performance.…”
Section: Fabrication and Properties Of The Ms Compositementioning
confidence: 96%
“…Miao et al 139 used thermoplastic polyurethane (TPU) as the matrix material and PAN as the binder. Fe 3 O 4 nanoparticles were uniformly locked on TPU/PAN nanofibers, and a magnetic fiber film with a high magnetization of 18.9 emu g −1 was prepared by electrospinning.…”
Section: Electrospun Mxene Nanosheet/polymer Compositesmentioning
confidence: 99%